RELIGIUSITAS DAN PROSES KREATIF A. MUSTOFA BISRI DALAM KUMPULAN CERPEN LUKISAN KALIGRAFI: KAJIAN SOSIOLOGI SASTRA - Ahmad Toni Ardi; Widowati Widowati (Universitas Sarjanawiyata Tamansiswa, 2019)
The purpose of this research is to describe and explain (1) plot, (2) figure and character, (3) setting, (4) reality of life from boarding school, (5) religiosity A. Mustofa Bisri, and (6) creative process A. Mustofa Bisri in anthology short story Lukisan Kaligrafi. The type of research used in this study is descriptive qualitative. The results obtained in this research area. (1) Plot used is a progress manner and flashback. (2) ) Figure and character is Gus Jakfar: always curious, figure ‘aku’: wise, Ustadz Bachri: not easily hopeless, humble, Kang Amin: not easily give up. Meanwhile is available figure additional that is Kiai Tawakkal, Nabi Khidir, Hardi, Kiai Nur, Samsuddin. (3) geographical settings in anthology short story Lukisan Kaligrafi: Sabilul Muttaqin Boarding School, Pesantren Bambu, house of figure ‘aku’, house of Ustadz Bachri, the warehouse of Ustadz Bachri, and exhibition location, Tanwirul ‘Uquul Boarding School, city of recitation location. The social setting is muslim society in rural and life of santri. Time setting is night and daytime. (4) the reality of life from boarding school in anthology short story Lukisan Kaligrafi seen from the interaction which becomes aware antartokoh and between relation kiai, santri, and family ndalem boarding school in layer santri society. (5) Religiosity A. Mustofa Bisri relevance in anthology short story Lukisan Kaligrafi seen from activities religious, as recitation or dakwah with all his experience which pictured all short story. (6) Creative process A. Mustofa Bisri in anthology short story Lukisan Kaligrafi be born and processed from the life of A. Mustofa Bisri which not far dakwah world.